Hospital outcomes of acute COVID-19 infection among patients with neurological conditions: a single-center study - Desouky, Adam; Fuentes, Venessa; Tiwari, Chhitij; Usui, Hikari; Smith Ayala, Arthor H.; Wilson, Susan E.; Diaz, Monica M. (Frontiers in Neurology, 2024)
COVID-19 infection has been associated with severe neurological consequences, including stroke or seizures, as well as less severe neurological sequelae including headaches, dizziness, and anosmia. Earlier COVID-19 variants were associated with high morbidity and mortality, however knowledge of impact of neurological conditions in the setting of COVID-19 on healthcare outcomes is limited. We sought to determine the impact of acute neurological conditions and acute COVID-19 infection on inpatient hospitalization outcomes.This was a retrospective, observational study of adult patients who were admitted to a large academic medical center in Southeastern US between April 2020 and December 2021 with acute COVID-19 infection and a neurological diagnosis. Patient demographics, medical history, neurological diagnoses, and hospitalization outcomes were recorded from the medical record.Descriptive statistics and unadjusted and adjusted logistic regression analyses were performed.Of 1387 patients included in this study, 27% died and 23% were ventilated during hospitalization. The mean +/-standard deviation (SD) age was 64.6+/-16.9 years with 52.8% females and 30.1% identifying as Black/African American. The most common neurological conditions included: ischemic stroke (35.0%), movement disorder (12.0%), and hemorrhagic stroke (10.7%). In-hospital death was most common among those with epilepsy (p=0.024), headache (p=0.026), and dementia (p<.0001) compared to not having those conditions.Ventilation was more common in dementia (p=0.020). Age was a significant risk factor for death (p<.001) and hospital length of stay for ventilation (p<.001), but no neurological condition was in adjusted logistic regression analyses.Mortality was high in this study with more than one-quarter dying in the hospital. Death was most common among those with epilepsy, headache, or dementia, but no neurological condition increased the risk of in-hospital mortality nor ventilation. Future studies would determine longterm neurological sequelae of those discharged from the hospital with COVID-19 and a neurological condition.